Perancangan Perancangan Media Pembelajaran Berbasis Game Menggunakan Aplikasi Scratch : Design of Game-Based Learning Media Using the Scratch Application - riska resa ayu; Liza Efriyanti; Supratman Zakir; Khairuddin (Universitas Sam Ratulangi, 2023)
Abstract — The design of Game-based learning media using the Scratch application is based on the results of interviews with teachers at SMA N 1 Junjung Sirih regarding the conventional learning model used, low student learning motivation. and have not optimized the use of learning media using technology. So learning looks monotonous and it is difficult to understand the material. The aim of this research is to produce Game-based learning media so that it produces valid, practical and effective learning media. This research uses the R&D (Research and Development) research method with development research using the 4D development model, namely Define, Design, Develop and Disseminate. The results of research on Game-based learning media products by testing product validity resulted in an average V value of 0.85 which was stated in the